IMPLEMENTATION OF LEGAL PROTECTION OF BRAND RIGHTS FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) ACCORDING TO LAW NUMBER 20 YEAR 2016 CONCERNING MARKS AND GEOGRAPHIC INDICATIONS - Puspa Melati Hasibuan; Zulfi Chairi; Aflah Aflah (UNIVERSITAS PAKUAN, 2022)
The legal protection of MSME product brands is the same as legal protection for other brand rights holders regulated in the 2016 UUM. The aim of this journal is to find out the legal arrangements for trademark rights in Indonesia and to find out the Legal Protection for Micro, Small and Medium Enterprises (MSMEs) according to the Law Number 20 Year 2016 concerning Brands and Geographical Indications. The research method used in this journal is normative juridical research with legal material collection techniques using literature studies and legal material analysis using content analysis. The results of the study show that the legal regulation of trademark rights in Indonesia consists of the International Convention on Marks ratified by Indonesia and Law Number 20 Year 2016 concerning Marks and Geographical Indications. Meanwhile, regarding the application of legal protection for Micro, Small, and Medium Enterprises (MSMEs), the existence of Law Number 20 Year 2016 concerning Marks and Geographical Indications is expected to be one of the government's ways in protecting UMKM businesses through the intellectual property in the form of a brand. With brand recognition given to MSME business actors, large industries or business actors who does not have good intentions, cannot automatically take intellectual property belonging to MSME business actors because the ownership of registered marks is recognized and protected by the government.